The use and discontinuation of hormone replacement therapy in women in South China. (2nd January 2018) - Chu, K.; Song, Y.; Chatooah, N. D.; Weng, Q.; Ying, Q.; Ma, L.; Qu, F.; Zhou, J.
Abstract: Objective: The use of hormone replacement therapy (HRT) started later in China than in European countries. The purpose of the present study was to investigate HRT patterns and reasons for the initiation and discontinuation of HRT among women in South China. Methods: A telephone survey about menopausal status, the use of HRT, reasons for HRT discontinuation and duration of HRT treatment was conducted in 2014. Results: A total of 825 telephone surveys were carried out, and 217 previous HRT users and 390 current users were recruited for this study. Among these 607 subjects, 50.7% of the women sought out HRT for hot flushes, 41.6% for fatigue and 41.5% for sleeplessness. Approximately one-third (35.9%) of the patients abandoned HRT during the following year. The reasons for stopping HRT were mainly fear of breast and uterine cancer (28.4%), reduced menopausal symptoms (22.9%) and the inconvenience of taking pills or seeing a doctor (17.9%). The factors related to HRT discontinuation were the age when HRT was initiated (odds ratio 1.59, 95% confidence interval 1.19–2.13) and education level (odds ratio 0.78, 95% confidence interval 0.62–0.98). Conclusions: The duration of HRT use in women in south China was short, and a high proportion of the women discontinued HRT. Given the high discontinuation rate and the low medical compliance, Chinese health-care providers still have much to do to let women know about the advantages and disadvantages of HRT and to encourage the use of HRT appropriately.